Repositioning Kiyai at Pesantren[s] in Political Dynamics of Nationality (An Analysis of Kyai's Role and Function in Modern Education System) - Qolbi Khoiri (Fakultas Ilmu Pendidikan UNP)
This paper aims to reveal and explain the dynamics of kiyai pesantren[s] in relation to national politics and to review the repositioning role of kiyai in the dynamics of national politics. Despite much analysis of the role of this kiyai, the fact that the tidal position of kiyai in pesantren[s] is increasingly seen its inconsistency. This can be evidenced by the involvement of kiyai practically in politics, thus affecting the existence of pesantren[s]. The results of the author's analysis illustrate that kiyai at this time must be returning to its central role as the main figure, it is important to be done, so that the existence of pesantren[s] in the era can be maintained and focus on reformulation of moral fortress and morality. The reformulation that authors offer is through internalization and adaptation of modern civilization and focus on improvements in educational institutions, both in the economic, socio-cultural, and technological.